Prevalence of Iron Deficiency Anemia in Anemic Patients: A Hospital Based Study - Mishra, Satyendra Kumar; Marasini, Surendra; Gupta, Badri Kumar; Agrawal, Krishna Kumar; Gautam, Narayan (Journal of universal college of medical sciences, 2018)
Introduction: In developing countries like Nepal, iron deficiency anemia (IDA) is one of the major concern. The high rate incidence has been related to insufficient  iron  intake, accompanied  by chronic  intestinal  blood  loss  due  to parasitic  and  malarial infections. Therefore, a study was conducted to evaluate the prevalence of IDA in anemic patients of Universal College of Medical Sciences-Teaching Hospital (UCMS-TH), South Western region, Nepal. Material and Method It was a hospital based cross sectional study comprised of 100 anemic patients. Their detailed medical history and lab investigations, focusing on hematological parameters were documented. Peripheral smear examination and serum ferritin estimation were done to observe red cell morphology and iron status respectively. Results: This study revealed that out of 100 anemic patients, 35% were that of IDA. The most affected age group was 21-40 years with frequency 42.55%. IDA was more common in females (42.85%) than in male (21.62%). Out of 100 anemic patients, microcytic hypochromic anemia was predominant in 47% followed by macrocytic anemia (31%) and then normocytic normochromic anemia (22%). Out of 47 microcytic hypochromic anemic patients, 12 had normal serum ferritin. There was a statistical significant difference in Hb (p=0.011), MCV (p=0.0001), MCH (p=0.0001), MCHC (p=0.0001) and serum ferritin (p=0.0001) among all types of anemia. There was a statistical significant positive correlation of ferritin with Hemoglobin (0.257, p= 0.01), MCV (0.772, p= 0.0001), MCH (0.741, p=0.0001) and MCHC (0.494, p=0.0001). Conclusion: The peripheral smear in conjunction with serum ferritin estimation needs to be included for susceptible individuals to screen the IDA and other types of anemia.